Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve the system of equations using substitution.
We are given two equations:
[tex]\[ \begin{array}{l} 1. \quad y = 2 + 3x \\ 2. \quad 4x - 3y = -16 \end{array} \][/tex]
Step 1: Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation. The first equation is already solved for [tex]\( y \)[/tex], so we have:
[tex]\[ y = 2 + 3x \][/tex]
Step 2: Substitute [tex]\( y = 2 + 3x \)[/tex] into the second equation:
[tex]\[ 4x - 3(2 + 3x) = -16 \][/tex]
Step 3: Distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ 4x - 6 - 9x = -16 \][/tex]
Step 4: Combine like terms on the left side:
[tex]\[ 4x - 9x - 6 = -16 \\ -5x - 6 = -16 \][/tex]
Step 5: Add 6 to both sides of the equation to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -5x = -16 + 6 \\ -5x = -10 \][/tex]
Step 6: Divide both sides by -5 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-10}{-5} \\ x = 2 \][/tex]
Step 7: Substitute [tex]\( x = 2 \)[/tex] back into the first equation ( [tex]\( y = 2 + 3x \)[/tex] ) to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 2 + 3(2) \\ y = 2 + 6 \\ y = 8 \][/tex]
Therefore, the solution to the system of equations is [tex]\((x, y) = (2, 8)\)[/tex].
So, the correct answer is:
[tex]\[ (2, 8) \][/tex]
We are given two equations:
[tex]\[ \begin{array}{l} 1. \quad y = 2 + 3x \\ 2. \quad 4x - 3y = -16 \end{array} \][/tex]
Step 1: Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation. The first equation is already solved for [tex]\( y \)[/tex], so we have:
[tex]\[ y = 2 + 3x \][/tex]
Step 2: Substitute [tex]\( y = 2 + 3x \)[/tex] into the second equation:
[tex]\[ 4x - 3(2 + 3x) = -16 \][/tex]
Step 3: Distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ 4x - 6 - 9x = -16 \][/tex]
Step 4: Combine like terms on the left side:
[tex]\[ 4x - 9x - 6 = -16 \\ -5x - 6 = -16 \][/tex]
Step 5: Add 6 to both sides of the equation to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -5x = -16 + 6 \\ -5x = -10 \][/tex]
Step 6: Divide both sides by -5 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-10}{-5} \\ x = 2 \][/tex]
Step 7: Substitute [tex]\( x = 2 \)[/tex] back into the first equation ( [tex]\( y = 2 + 3x \)[/tex] ) to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 2 + 3(2) \\ y = 2 + 6 \\ y = 8 \][/tex]
Therefore, the solution to the system of equations is [tex]\((x, y) = (2, 8)\)[/tex].
So, the correct answer is:
[tex]\[ (2, 8) \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.